Global solver for nonlinear bilevel vector optimization problems - Jahn, Johannes; Gebhardt, E. (Pacific Journal of Optimization, 2009)
Optimality conditions are given for nonlinear bilevel vector optimization problems in infinite dimensions. A new numerical method based on a multiobjective search algorithm with subdivision technique, is introduced for the determination of global solutions. Numerical results are presented for low dimensional nonlinear problems. © 2009 Yokohama Publishers.
UnivIS-Import:2015-03-09:Pub.2009.nat.dma.pama21.global
Keywords: Bilevel optimization; Global solvers; Vector optimization